Reading Scepticism Historically. Scepticism, Acatalepsia and the Fall of Adam in Francis Bacon - Manzo, Silvia (2017)
The first part of this paper will provide a reconstruction of Francis Bacon's interpretation of Academic scepticism, Pyrrhonism, and Dogmatism, and its sources throughout his large corpus. It shall also analyze Bacon's approach against the background of his intellectual milieu, looking particularly at Renaissance readings of scepticism as developed by Guillaume Salluste du Bartas, Pierre de la Primaudaye, Fulke Greville, and John Davies. It shall show that although Bacon made more references to Academic than to Pyrrhonian Scepticism, like most of his contemporaries, he often misrepresented and mixed the doctrinal components of both currents. The second part of the paper shall offer a complete chronological survey of Bacon's assessment of scepticism throughout his writings. Following the lead of previous studies by other scholars, I shall support the view that, while he approved of the state of doubt and the suspension of judgment as a provisional necessary stage in the pursuit of knowledge, he rejected the notion of acatalepsia. To this received reading, I shall add the suggestion that Bacon's criticism of acatalepsia ultimately depends on his view of the historical conditions that surround human nature. I deal with this last point in the third part of the paper, where I shall argue that Bacon's evaluation of scepticism relied on his adoption of a Protestant and Augustinian view of human nature that informed his overall interpretation of the history of humanity and nature, including the sceptical schools.